The Optimal Time for Applying 5%Lidocaine Medicated Plaster to Decrease Protective Sensation of Skin - Ruananukun, Narut (Thai Journal of Anesthesiology, 2021)
Background: Eutectic mixture of local anesthetics is commonly used to reduce pain during cutaneous interventions but it must be applied under an occlusive bandage. It can cause vasoconstriction, methemoglobinemia and skin wrinkling. Five percent lidocaine medicated plaster (5%LMP), which is indicated for neuropathic pain, may be an alternative topical anesthetic. However, there is no data about its relationship between time and level of decreasing protective sensation of skin. Objective: To determine the optimal time for applying 5%LMP to decrease protective sensation of skin. Materials and Methods: Twenty healthy adult volunteers were tested for baseline sensation at dorsum of hand by the Semmes-Weinstein monofilaments kit, then they were tested hourly for 8 hours after applied 5%LMP. Sensory levels were recorded as A-level to T-level which G-level means diminish protective sensation. The main result was the onset time which defined as the time when G-level monofilament cannot be detected. The median time of the onset was analyzed. Results: The volunteers were 10 for each sex and their mean age was 30.65 + 5.9 years. All male volunteers were able to reach G-level, but females were 30% fail to reach the G-level within 8 hours. The median onset time was 5 hours (95%CI:2.809-7.191) but there was different between male and female (P=0.000); which were 3 hours (95%CI:1.482- 4.518) and 7 hours (95%CI:4.934-9.006) respectively. No skin wrinkling or any complications were observed. Conclusion: Applying 5%LMP to decrease protective sensation of skin takes at least 5 hours. This may take longer time in female